Study on Layered-Backfill-Based Water Protection Technology of Thick Coal Seam in the Ecologically Fragile Mining Area in Western China. (9th August 2022) - Zhu, Lei; Song, Tianqi; Gu, Wenzhe; Xu, Kai; Liu, Zhicheng; Qiu, Fengqi; Zhang, Xinfu
Abstract : The mining areas in Western China are characterized by water shortage and ecological fragility, and the coal resources in these areas are extracted in a large-scale and highly intensive manner, which is highly likely to induce ecological problems, such as soil erosion and grassland degradation. In addition, there is a secondary protection zone of Hongshixia water source near Guojiatan minefield. If the water resources loss of Salawusu Formation is too large, it will affect the normal water supply of Yulin city. To reasonably coordinate coal exploitation and water protection, the development characteristics of water-conducted fissures with different backfill ratios are obtained in combination with theoretical analysis, field test, and numerical modelling. The panel layout of the layered-backfill-based water protection working face and the parallel operation of mining and backfilling are designed, and a feedback regulation system integrating hydrological monitoring and backfill ratios is established, which assists in evaluating the effectiveness of water protection. The results indicated that when the slicing mining method was adopted with the roof naturally caving, the maximum development height of the water conducted fracture zone was 220.0 m (developed to the Yan'an Formation), and the water conducted fracture zone could only develop to the Yan'an Formation without crossing the Zhiluo Formation when the backfill ratio reached 80%. The water emission rates in the west of the field testing area reduced from 334.95 m 3 /h to 60.60 m 3 /h, dropping by 86.86%. Compared to the scene prior to the layered backfill mining, the shallow water outflow was reduced by 72.74 m 3 /h, and it helped annually reduce the shallow water loss of 637200 m 3, which was equivalent to 1.74% of the actual water supply to Yunli city every year. The results of this study can provide guidance on effectively avoiding the loss of shallow water resources that are regarded as indispensable sources of domestic water.